The effect of prevention methods on reducing sexual risk for HIV and their potential impact on a large-scale: a literature review - Alexandre Grangeiro; Dulce Ferraz; Gabriela Calazans; Eliana Miura Zucchi; Ximena Pamela Díaz-Bermúdez (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2015)
ABSTRACTA spectrum of diverse prevention methods that offer high protection against HIV has posed the following challenge: how can national AIDS policies with high coverage for prevention and treatment make the best use of new methods so as to reverse the current high, and even rising, incidence rates among specific social groups? We conducted a narrative review of the literature to examine the prevention methods and the structural interventions that can have a higher impact on incidence rates in the context of socially and geographically concentrated epidemics. Evidence on the protective effect of the methods against sexual exposure to HIV, as well as their limits and potential, is discussed. The availability and effectiveness of prevention methods have been hindered by structural and psychosocial barriers such as obstacles to adherence, inconsistent use over time, or only when individuals perceive themselves at higher risk. The most affected individuals and social groups have presented limited or absence of use of methods as this is moderated by values, prevention needs, and life circumstances. As a result, a substantial impact on the epidemic cannot be achieved by one method alone. Programs based on the complementarity of methods, the psychosocial aspects affecting their use and the mitigation of structural barriers may have the highest impact on incidence rates, especially if participation and community mobilization are part of their planning and implementation.